1999
DOI: 10.1136/thx.54.7.606
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of atopy, asthma symptoms and diagnosis, and the management of asthma: comparison of an affluent and a non-affluent country

Abstract: Background-The prevalence of childhood asthma and of atopy varies widely between countries. However, few studies have compared the pattern of diagnosis and management of asthma, or the role of atopy in predisposing to asthma between a less aZuent country and a more aZuent country. The aim of this study was to compare the prevalence of symptoms, diagnosis, and management of asthma, and the prevalence of atopy as measured by skin prick tests in Nigeria and Australia using a standardised methodology. Methods-Resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
3
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 18 publications
(8 reference statements)
8
39
3
1
Order By: Relevance
“…10,28,[37][38][39][40] There is no explanation for the finding. According to Rona,18 poverty is not a risk factor for the appearance of asthma, but an aggravating factor.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…10,28,[37][38][39][40] There is no explanation for the finding. According to Rona,18 poverty is not a risk factor for the appearance of asthma, but an aggravating factor.…”
Section: Discussionmentioning
confidence: 43%
“…19 The metropolitan region produces the following air pollutants monthly: 1,000 tons of airborne particles, 351 tons of sulphur dioxide , 45 tons of nitrous oxide, 33 tons of hydrocarbons and 336 tons of carbon monoxide. 20 According to the IBGE 2000 census, 40.8% of the inhabitants of Recife aged more than 20 years had not completed four years schooling. 21 Both the sample of schoolchildren from 1994-95 and that from 2002 were selected in a probabilistic manner.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, 37.4% of the study population had positive SPT to common allergens (44.1% of subjects and 31.2% of controls). Thus, the prevalence of atopy is similar to that in the general population [22]. In the study by Garrett et al, positive reactions to extracts in skin prick testing were more common at higher levels of contamination with Cladosporium or Penicillium.…”
Section: Discussionmentioning
confidence: 53%
“…Studies performed in areas where infectious diseases are still highly prevalent indicated that the prevalence of allergy in such less-developed parts of the world is indeed lower than in western societies. For example, in different African countries the prevalence of self-reported asthma, allergic rhinoconjunctivitis as well as atopic eczema was less than 5% [2, 3, 4], which is clearly lower than that reported in the west [2]. Additionally, the prevalence of allergic disorders in developing countries is higher in urban than in rural settings, indicating that the development of allergy is associated with a more western lifestyle [3].…”
Section: Introductionmentioning
confidence: 94%